INTERVAL-VALUED INTUITIONISTIC FUZZY SUBSEMIMODULES WITH (S,T)-NORMS - Hedayati, H. (Italian Journal of Pure and Applied Mathematics, 2010)
On the basis of the concept of the interval valued intuitionistic fuzzy sets introduced by K. Atanassov, the notion of interval valued intuitionistic fuzzy subsemimodule of a semimodule with respect to t-norm T and s-norm S is given and the characteristic properties are described. The homomorphic image and inverse image are investigated. In particular, by the help of the congruence relations on semimodules, new interval valued intuitionistic (S,T)-fuzzy subsemimodules are constructed.